Digital Disruption in Transportation: Gojek's Entry and Growth in Makassar (2015-2020) - Al Islami, Achmad Idrus; Choerunnisa, Arinda (Yupa: Historical Studies Journal, 2025)
PT. Gojek Indonesia, a technology company founded in 2011 by Nadiem Makarim and Kevin Aluwi, introduced online transportation services to Indonesia, starting with GoRide, a modern motorcycle taxi service. This research employs a historical method with four steps: Heuristics, Criticism, Interpretation, and Historiography. Gojek officially began operations on August 8, 2015, receiving an enthusiastic response from the public. Its presence improved urban mobility, offering easy access and affordable rates, supported by professional and friendly drivers. Unlike traditional motorcycle taxis, Gojek provides both passenger and goods transportation services, as well as shopping and food delivery options. The Gojek application offers various services, including GoRide, GoSend, GoFood, GoCar, GoMart, and GoBox.. Gojek's entry into Makassar aimed to alleviate traffic congestion and improve mobility in the city. The company obtained necessary permits and coordinated with relevant stakeholders before launching its services. Gojek's presence has significantly impacted the transportation landscape in Makassar, providing a convenient, affordable, and reliable alternative to traditional transportation modes while also contributing to job creation and economic growth.